Innovative Catalytic Systems for Methane Steam Reforming Intensification - V. Palma; A. Ricca; M. Martino; E. Meloni (Chemical Engineering Transactions, 2016)
Structured catalysts based on highly conductive carriers, can improve the heat transfer along the catalytic bed, allowing a flattened radial temperature gradient and a consequently higher performance. The effect of thermal conductivity of structured carriers on highly endothermic Methane Steam Reforming (MSR) reaction is investigated. The performance of the structured catalysts, obtained on Cordierite and Silicon Carbide (SiC) monoliths, demonstrates the direct correlation between the thermal conductivity of the carrier, the methane conversion and the hydrogen productivity. The evaluation of the monolith configuration shows that the SiC “wall flow” (WF) guarantees a better axial and radial thermal distribution, with respect to the SiC “flow through” (FT), resulting in better catalytic activity up to a temperature reaction of 750 °C. The comparison among the performance of the structured catalysts and the commercial 57-4MQ, provided by Katalco-JM, highlights the choice of structured catalysts, which require a lower temperature outside of the reactor, increasing the process efficiency.